Vaccination of healthcare workers against influenza: does a day off make a difference?. Issue 2 (June 2018) - Maltezou, H.C.; Christophilea, O.; Tedoma, A.; Katerelos, P.; Dounias, G.
Summary: This article presents the results of actions undertaken to increase influenza vaccine uptake by healthcare workers (HCWs) in Greece during the 2016–2017 influenza season. Influenza vaccination among HCWs increased from 10.9% in acute care hospitals and 24.3% in primary healthcare centres in 2015–2016 to 18% in acute care hospitals and 34.6% in primary healthcare centers in 2016–2017. Vaccination on site at the healthcare facility and use of reward systems were significantly associated with increased vaccination rates. Offering vaccinated HCWs one day off work was associated with the greatest increase in influenza vaccine uptake.